Knowledge-based Economy, an Appropriate Response to Organizational Change Pressures, with a View to Sustainable Development - Cristina Mihaela Lazar; Ramona Nicoleta Bunda (Amfiteatru Economic)
The sustainable development of organizations within knowledge-based economy, in which knowledge represents the main priority, should focus on finding solutions for the intelligent management of the limited resources, especially through organizational change and its constant assessment as a long-term impact solution. The transition of organizations to the principles of knowledge-based economy involves a major change in organizational culture. The dynamism and complexity of the new type of society, which implies a higher and more diverse level of training, together with a continuous superior training of the workforce, increasing investment in research and development and, not least, a growing volume and a diversification of information, all these represent, chained together, an element of well-being for the future generations. The introductory section summarizes the concept of sustainability and places the development of companies and economies they aggregate, in a contemporary context of organizational change pressures, on the principles of the knowledge-based economy as the only resource, virtually inexhaustible in the long-term, and which leads to a sustainable development. There follows a methodological section, consisting in the instrumental description of the method of work and in reference to the database, thus providing the theoretical and practical foundation for the confrontation between the sustainable development index (SDI) in Romania and in the European Union (EU). The results and discussion section of the paper includes a confrontation between the sustainable development of Romania and that of the European Union, drawing on the SDI for each case. This statistical tool was calculated starting from the values of several statistical indicators (available in EUROSTAT statistics), issued from four information subsystems (an economic one, a social one and an environment one as major subsystems of sustainable development, to which was added the institutional environment). The SDI confirms a considerable gap between Romania and the EU-27 average, and the organizational change on the principles of knowledge-based economy is emerging as the optimal solution and gradual recovery of these gaps.